PENGARUH KUALITAS JASA DAN HARGA TERHADAP KEPUASAN PELANGGAN CENGKARENG GOLF CLUB - Atik Atikah; Doddy Mulyono (Bussman Journal : Indonesian Journal of Business and Management, 2021)
The sample used as respondents is 75 people who are members of the Cengkareng Golf Club. The main data collection technique is by using a questionnaire regarding service quality variables, price variables and customer satisfaction variables. The data analysis technique used is correlation analysis and multiple correlation, determination coefficient analysis and simple regression analysis and multiple regression. The results of the study resulted in a conclusion that there was a significant effect of service quality on customer satisfaction at Cengkareng Golf Club. There is a significant price effect on customer satisfaction. There is a significant influence simultaneously service quality and price on customer satisfaction. At this time the service quality of Cengkareng Golf Club is good enough, to improve the quality of golf services, it is suggested that service quality can be used as a strategy to increase customer satisfaction through providing appropriate services to customers, responding and customer requests quickly, handling customer problems, and provide customer satisfaction provided not only in the form of physical facilities, but the appearance of a professional employee. Currently customer satisfaction is categorized as good enough by paying attention to the quality of services and prices provided to customers, so that customer satisfaction increases, it is recommended that Cengkareng Golf Club pay attention to the factors that make customers buy back, create word of mouth marketing carried out by customers, improve brand image Cengkareng Golf Club and pay attention to customer decision-making factors when playing golf in addition to service quality and price factors